Determinan Kinerja Guru SMK Negeri 1 Gunung Talang, Kabupaten Solok, Kenagarian Talang - Sriyanti, Esi; Arfimasri, Arfimasri; Yuldesnita, Putri (Jurnal Tinta, 2025)
Teacher performance should be further improved to produce highly capable human resources in the increasingly competitive global era. Job training, which is a process of improving work competency, affects teacher performance. Supervision and educational training through management, administration, and leadership agendas depend on the school leader. Due to their complexity, schools need coordination. The success of the school also depends on the success of the principal. This study investigated teachers at SMK Negeri 1 Gunung Talang and aimed to determine whether there was a relationship between training and leadership and teacher performance at the school. This type of research is called quantitative research. The data used is qualitative . This study used a total sampling method on a population of 56 respondents, which included all teachers at SMKN 1 Gunung Talang. The results of the statistical analysis showed that training and leadership partially had a significant effect on the performance of teachers at SMK Negeri 1 Gunung Talang. Then, training and leadership simultaneously influenced the performance of teachers at SMK Negeri 1 Gunung Talang. In addition, the R-squared value increased to 0.575, or 57.5%, which indicates that additional variables not discussed in this study affect the majority.